The Warburg Effect in Yeast: Repression of Mitochondrial Metabolism Is Not a Prerequisite to Promote Cell Proliferation - Bouchez, Cyrielle L.; Hammad, Noureddine; Cuvellier, Sylvain; Ransac, Stéphane; Rigoulet, Michel; Devin, Anne (Frontiers in Oncology, 2020)
O. Warburg conducted one of the first studies on tumor energy metabolism. His early discoveries pointed out that cancer cells display a decreased respiration and an increased glycolysis proportional to the increase in their growth rate, suggesting that they depend mainly on fermentative metabolism for ATP generation. Warburg’s results and hypothesis generated controversies that are persistent to this day. It is thus of great importance to understand the mechanisms by which cancer cells can reversibly regulate the two pathways of their energy metabolism as well as the functioning of this metabolism in cell proliferation. Here, we made use of yeast as a model to study the Warburg effect and its eventual function in supporting an increased ATP demand to support cell proliferation. The role of oxidative phosphorylation repression in this effect was investigated. We show that yeast is a good model to study the Warburg effect, where all parameters and their modulation in the presence of glucose can be reconstituted. Moreover, we show that in this model mitochondria are not dysfunctional: there is fewer mitochondria respiratory chain units per cell. Identification of the molecular mechanisms involved in this process allowed us to dissociate the parameters involved in the Warburg effect and show that oxidative phosphorylation repression is not mandatory to promote cell growth. Last but not least, we were able to show that neither cellular ATP synthesis flux nor glucose consumption flux control cellular growth rate.